Screening by single-molecule molecular inversion probes targeted sequencing panel of candidate genes of infertility in azoospermic infertile Jordanian males. (20th October 2022) - Batiha, Osamah; Burghel, George J.; Alkofahi, Ayesha; Alsharu, Emad; Smith, Hannah; Alobaidi, Bilal; Al-Smadi, Mohammad; Awamlah, Nour; Hussein, Lama; Abdelnour, Amid; Sheth, Harsh; Veltman, Joris
Abstract: Infertility is a common health problem that affects around 1 in 6 couples in the United States, where half of these cases are attributed to male factors. Genetics play an important role in infertility and it is estimated that up to 50% of cases are due to genetic factors. Despite this, many male infertility cases are still idiopathic. This study aimed to identify the presence of possibly pathogenic rare variants in a set of candidate genes related to azoospermia in 69 Jordanian men using a next-generation sequencing-based panel covering more than a hundred male infertility related genes. A total of 9 variants were found and validated. Among them, two variants included reported pathogenic variants in CFTR and one novel pathogenic variant in the USP9Y gene. We also report the detection of 6 other variants with uncertain significance in other genes. Interestingly, male cases with CFTR variants did not show the expected cystic fibrosis phenotypes except for infertility. This work helps to uncover the contribution of additional genetic factors to the aetiology of male infertility and highlights the importance to obtain more reliable information about the presence of genetic variation in the Jordanian population.